Congenital Cystic Adenomatoid Malformation: Is There a Need for Pregnancy Termination?. (14th March 2012) - Iavazzo, C.; Eleftheriades, M.; Bacanu, A. M.; Hassiakos, D.; Botsis, D.
Abstract : Aim . Congenital cystic adenomatoid lung malformation is a rare unilateral dysplasia of the lung. Three pathologic types are described in the literature: type I with cysts >2 cm, type II with cysts <1 cm, and type III with microcysts. The aim of this paper is to present a case of a fetus with congenital cystic adenomatoid lung malformation and discuss the necessity for pregnancy termination according to its prognosis and future mortality. Case . A 36-year-old pregnant woman (para: 1, gravida: 1) presented in our department for anatomy ultrasound screening at20 + 1 weeks of gestation. The ultrasound detected a cystic adenomatoid right lung malformation measuring1.45 × 1.67  cm which caused mediastinal shift of the heart and the lung to the left side. Other findings were cysts of the choroid plexus and echogenic intracardiac foci. The parents after genetic counseling decided pregnancy termination. The pregnant received cabergoline for ablactation. Conclusion . Congenital cystic adenomatoid lung malformation has different prognosis according to the type (69% in type I, 0% in types II and III). Fetal hydrops, cardiac and skeletal anomalies, Potter's syndrome, and gastrointestinal atresia are common cofindings. Genetic counseling is necessary, and pregnancy termination is proposed to the cases with poor prognosis.